RESPUESTAS DEL INSECTO MAX (SCYPHOPHORUS ACUPUNCTATUS GYLLENHAL [COLEOPTERA: CURCULIONIDAE]) HACIA ALGUNOS COMPUESTOS ATRAYENTES DEL HENEQUÉN - Valdés Rodríguez, Silvia; Ramirez Choza, José Luis; Reyes Lopez, Jorge; Blanco Labra, Alejandro (Instituto de Ecología, A.C., 2004)
Scyphophorus acupunctatus Gyllenhal 1838 (Coleoptera: Curculionidae) is one of the most important pests of cultivated agave, causing severe damage to the leaves of the plant. Yield losses up to 40% have been reported due to this insect. Previous studies have shown the attractive effect of henequen leaves towards the insect S. acupunctatus and the effective control of this pest using henequen leaves treated with common insecticides. Therefore, this study was undertaken to identify the compounds responsible for the strong attraction towards the insect S. acupunctatus. Henequen leaves were steam distilled and subsequently extracted with different organic solvents. Free choice bioassays were conducted to determine the attractive activity of each extract towards this insect, using groups of insects separeted on the basis of their sex, or else, taken at random. Statistical analysis showed significant differences among the different extracts tested. The five main compounds from the most active extracts determined by GC-MS were: 4-ethyl cumene, p-metoxy-ethyl benzene, 1(methyl 4-(1-methyl ethyl) cyclohexanol, p-mentha-1,5- dien-8-ol and butirofenone. Since these compounds are commercially available, it raises the possibility of using them in the control of this pest.